Synthesis and Characterization of Acetonitrile Ligated Cu(II)-Complex and Its Catalytic Application for Transesterification of Frying Oil in Heterogeneous Phase - Rycce Sylviana Pratikha; Syukri Syukri; Admi Admi (Universitas Gadjah Mada, 2013)
Catalysts have played an important role in many industries because they allow the reaction occurs faster. The aim of this work were to synthesize and characterize a Cu(II)-acetonitrile complex immobilized on modified silica and to investigate its catalytic activity at optimal condition (catalyst concentration, stirring rate, and the duration of reaction) in transesterification of frying oil. Fourier Transform Infrared (FTIR) and Nano Laser-Particle Size Analyzer (NL-PSA) were used to characterized the catalyst obtained, metal loading and leaching of the copper content was measured by Atomic Absorption Spectroscopy (AAS) and the formation of product from transesterification reaction was analyzed by Gas Chromatography-Mass Spectroscopy (GC-MS). FTIR spectra reveal a successful synthesis of modified silica and the immobilized Cu(II)-acetonitrile complex on it. NL-PSA Analysis showed that the catalyst possesed smaller particle size than the parent silica. Analysis with AAS confirms the stable catalysts formed because metal loading and leaching value were of 6.19 and 0.16%, respectively. The optimum conditions were found to be 0.80% catalyst concentration, 300 rpm stirring rate and 10 h duration of reaction.